Incorporação de triclosan e laranja de acridina em lipossomas para avaliação da susceptibilidade de Candida albicans - Romio, Karla Belissa (2015)
Drug delivery systems consisting of drugs encapsulated by liposomes (lipid vesicles) have attracted significant interest in recent years due to the possibility of their use in biomedical applications. Liposomes, able to act as carriers of antibiotics, have been widely used in studies involving biofilm formation in oral cavity. Ultrathin films are widely studied because they have molecular structural organization and can be applied in biosensors, optical devices, coatings and other materials. In this work, we have used the premise of assembly layer-bylayer technique, LBL, in order to immobilize triclosan and acridine orange encapsulated by liposomes. Fungus Candida albicans is responsible for most of the nosocomial infections which affect immunocompromised individuals. Although most Candida albicans are susceptible to antifungal drugs, uncontrolled use of drugs has promoted the development of resistance and tolerance to fungal pathogens with current antifungals. The clinical implication of the appearance of resistant strains is the search for safer and more effective drugs and also alternative therapies, such as antimicrobial photodynamic, which aims to eliminate the pathogen by the combination of light and photosensitizer. The effects of the laser irradiation on LBL films were investigated by using fluorescence, atomic force microscopy and release kinetics. The susceptibility of the fungi Candida albicans was evaluated in photodynamic experiments using a laser light (470nm). After the irradiations, morphological changes on fungi surfaces were observed. This was attributed to cellular damage of the outer membranes as a result of a photodynamic effect and TCS properties. The result depended on dialysis process and indicated susceptibility of fungus. The release of triclosan occurs more quickly when the LBL film is irradiated. This kind of investigation can be a starting point in the search for new clinical strategies in order to control resistant strains.